Effects of genetic and non genetic factors on production performance of primiparous Kankrej cattle - Thakkar, N K; Chaudhary, AP; Chaudhari, AB; Gami, YM; Panchasara, HH (Indian Journal of Dairy Science, 2021)
The present investigation included the records of 294 Kankrej cows, sired by 66 sires spread over a period of 20 years (1996 to 2015) maintained at Livestock Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat. The effects of genetic and non genetic factors on performance traits (Daily Milk Yield, 305 Days Milk Yield, Total Milk Yield and Lactation Length) of primiparous Kankrej cows was studied. The least square means of daily milk yield, 305 days milk yield, total milk yield and lactation length were calculated and found 6.71±0.14, 1893.42±60.00, 1983.29±72.47 kg and 290.78±7.33 days, respectively. The season and period of calving did not affect these traits, while effects of sire was significant (*P